Permeability properties of plastics and elastomers - McKeen, Laurence W. (William Andrew Pub., 2017)
Permeability Properties of Plastics and Elastomers, Fourth Edition provides a comprehensive collection of graphical multipoint and tabular data covering the permeation of liquids, vapors, and gases through plastic or polymeric materials, such as films, membranes, and containers. This updated edition includes an entirely new chapter on sustainable and biodegradable polymers and an extensive introductory section covering fatigue, what it is, how it is measured, and the fundamentals of permeation and permeability properties. Foundational information is also provided on the production of films, containers, membranes, and the markets and applications for these materials
Keywords: TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Plastics / Permeability; Plastics -- Permeability; Elastomers -- Permeability; Permeabilität; Kunststoff; Datensammlung